2012
DOI: 10.1002/chem.201200513
|View full text |Cite
|
Sign up to set email alerts
|

Non‐aqueous Synthesis of Isotropic and Anisotropic Actinide Oxide Nanocrystals

Abstract: Nano is everywhere but actinides are the forgotten elements of the nanoworld! Isotropic faceted uranium oxide nanodots and anisotropic thorium oxide nanorods were synthesized. These nano‐objects are very well crystallized and monodisperse. The characteristics of the actinide oxide nanocrystals can be controlled by tuning the reactivity of the starting actinide precursors. Such results pave the way for the synthesis of transuranium‐based nano‐objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 51 publications
(14 reference statements)
3
57
0
Order By: Relevance
“…Fig. 7 shows the SEM images of the samples prepared at different temperatures under otherwise 50 identical conditions (Table 1, sample [17][18][19]. No product was obtained at 80 °C, suggesting the incomplete decomposition of HMTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 7 shows the SEM images of the samples prepared at different temperatures under otherwise 50 identical conditions (Table 1, sample [17][18][19]. No product was obtained at 80 °C, suggesting the incomplete decomposition of HMTA.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, thorium dioxide, a very important inorganic material in nuclear industry and catalysis, has been prepared using various methods [11][12][13][14][15][16] . For example, different morphologies of small ThO 2 25 nanocrystals, such as branched nanocrystals, nanodots and nanorods, have been synthesized through an organic-phase thermolysis method using thorium acetate and thorium acetylacetonate as the metal source in a mixture solution of oleic acid, oleylamine and octadecene 17,18 . This method has been 30 extended to the synthesis of other actinide oxide nanocrystals, such as UO 2 , NpO 2 , PuO 2 and the mixing oxide of thorium/uranium nanocrystals [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Hudry and co-workers demonstrated such a possibility with the Rietveld refinement of the crystal structure of ultrasmall thorium, uranium, and plutonium oxide NCs based on the bulk face-centered cubic (fcc) structure (space group Fm3̅ m). 31,58 The results showed that these ultrasmall NCs adopt a crystal structure that is very close to the bulk one. Nevertheless, large atomic displacement parameters of actinide atoms (unusual for such heavy atoms) suggest deviations from the average bulk structure, which were not quantified.…”
Section: Chemistry Of Materialsmentioning
confidence: 89%
“…Although the state of the art in this emerging field is still far from the level of complexity that has been reached for stable element‐based nanocrystals (i.e., noble metals, transition metals and rare‐earth elements), achievements in the wet‐chemical preparation of well‐defined actinide‐based nano‐objects have been reported over the past decade. For example, the non‐aqueous colloidal synthesis of uranium oxide nanocrystals was first proposed by Cao and co‐workers and was extended to thorium oxide by our group 5. 6 Additionally, heterodimer uranium oxide/indium oxide nanocrystals were successfully synthesised 7.…”
Section: Introductionmentioning
confidence: 99%